AIE-active organic resonance molecules for highly sensitive dynamic explosive detection. Issue 21 (19th May 2022) - Jiang, He; Zhang, Longyan; Xian, Lijie; Wang, Zijie; Jin, Jibiao; Zheng, Chao; Chen, Runfeng
Abstract : AIE-active resonance molecules designed by rational integration of AIE and resonance units show enhanced emission for dynamic self-adaptive high-performance explosive detection. Abstract : Organic materials with efficient aggregation-induced emission (AIE) are important for optoelectronic applications because of their significantly enhanced luminescence in the solid state. Here, we develop a series of high-luminescence molecules with both AIE and dynamic self-adaptive resonance features by combining the resonance linkage and the AIE-active unit. The prepared resonance molecules show impressive photoluminescence characteristics with a high quantum yield of 84% in the solid state. When employing them as the sensors for picric acid (PA), superior detection performance with a Stern–Volmer quenching constant of 1.33 × 10 5 M −1 and a limit of detection of 31 nM were observed. The facile resonance variation between N–PS and N + P–S − canonical forms in establishing strong and self-adaptive interactions with PA was found to be the main reason for the high-performance dynamic detection. These results highlight the successful design of highly luminescent resonance molecules, offering important guidelines in the development of new-concept sensors with dynamically tuned optoelectronic properties for self-adaptive sensing.